2009
DOI: 10.1159/000225661
|View full text |Cite
|
Sign up to set email alerts
|

Pentosidine – A New Biochemical Marker in Diabetic Retinopathy

Abstract: Aim: This study was done to evaluate the role of pentosidine in predicting the progression of diabetic retinopathy. Patients and Methods: We included 30 subjects with insulin-dependent diabetes mellitus (type 1) and 10 healthy control individuals. A case control study was done. Full ophthalmological examination together with laboratory investigations (blood glucose level, HbA1C and blood pentosidine level corrected to blood total protein values were measured) were done in all subjects included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 10 publications
2
12
1
Order By: Relevance
“…Thus, high sRAGE/pentosidine ratio among the DR patients may be used to predict the severity of DR. With the finding of sRAGE/pentosidine ratio as a significant determinant for DR (Table 4), this study suggests that sRAGE/pentosidine ratio could serve as a risk factor for DR among type 2 DM patients. In contrast to a previous report [18], pentosidine level was not significantly different between DR and DNR patients in this study. This could be explained by the variation in patient populations [19].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, high sRAGE/pentosidine ratio among the DR patients may be used to predict the severity of DR. With the finding of sRAGE/pentosidine ratio as a significant determinant for DR (Table 4), this study suggests that sRAGE/pentosidine ratio could serve as a risk factor for DR among type 2 DM patients. In contrast to a previous report [18], pentosidine level was not significantly different between DR and DNR patients in this study. This could be explained by the variation in patient populations [19].…”
Section: Discussioncontrasting
confidence: 99%
“…This could be explained by the variation in patient populations [19]. Our patients were of type 2 DM, older and had higher HbA 1c level when compared to the patients recruited in a previous study [18]. The patient groups (DNR and DR) in this study consisted of a significant number of Indian subjects when compared to the healthy controls as it was not possible to obtain significant healthy Indian volunteers in the age-group of interest.…”
Section: Discussionmentioning
confidence: 99%
“…For pentosidine, as a type of AGE, the study of Salman et al was done to evaluate the role of pentosidine in predicting the progression of DR. The authors showed that significant elevation of pentosidine was found in patients during the earliest detectable phase of DR (early nonproliferative diabetic retinopathy) and more elevation at the preproliferative stage of retinopathy, returning to lower levels at the proliferative stage of diabetic retinopathy (Salman et al, 2009). However, our results showed that pentosidine levels were increased in diabetic patients with proliferative stage of DR.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is regarded as one of the candidate genes involved in the development of DR, since it is expressed by critical tissues such as endothelium, smooth muscle, mesangial cells, and monocytes (Hudson et al, 2001). Advanced glycation end products (AGEs), which are well known to accumulate in retinopathy patients (Salman et al, 2009), are one of the endogenous ligands recognized by RAGE. They are complex, heterogenous molecules formed from non-enzymatic glycation and oxidation of proteins, lipids and nucleic acids (Bierhaus et al, 2005;Basta, 2008).…”
Section: Introductionmentioning
confidence: 99%